The Accuracy of Near Infrared Autofluorescence in Identifying Parathyroid Gland During Thyroid and Parathyroid Surgery: A Meta-Analysis - Wang, Bin; Zhu, Chun-Rong; Liu, Hong; Yao, Xin-Min; Wu, Jian (Frontiers in Endocrinology, 2021)
Objective. We aim to assess the accuracy of near infrared autofluorescence in identifying parathyroid gland during thyroid and parathyroid surgery. Method. A systematic literature search was conducted by using PubMed, Embase, and the Cochrane Library electronic databases for studies that were published up to February 2021. The reference lists of the retrieved articles were also reviewed. Two authors independently assessed the methodological quality and extracted the data. A random-effects model was used to calculate the combined variable. Publication bias in these studies was evaluated with the Deeks’ funnel plots. Result. A total of 24 studies involving 2,062 patients and 6,680 specimens were included for the meta-analysis. The overall combined sensitivity and specificity, and the area under curve of near infrared autofluorescence were 0.96, 0.96, and 0.99, respectively. Significant heterogeneities were presented (Sen: I2 = 87.97%, Spe: I2 = 65.38%). In the subgroup of thyroid surgery, the combined sensitivity and specificity, and the area under curve of near infrared autofluorescence was 0.98, 0.99, and 0.99, respectively, and the heterogeneities were moderate (Sen: I2 = 59.71%, Spe: I2 = 67.65%). Conclusion. Near infrared autofluorescence is an excellent indicator for identifying parathyroid gland during thyroid and parathyroid surgery.